Soft Power Politics of China: A Study of China-Sri Lanka Relations - Ganeshalingam, K.T. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
This paper examines the soft power politics of China in China-Sri Lanka relations focusing on the economic, political and military dimensions of the ties between the two countries. Sri Lanka’s strategic location in the centre of the Indian Ocean has attracted China's attention. China aims to achieve global control over the Indian Ocean by using Sri Lanka. The concept of ‘Soft Power’ rests on a country’s ability to recognize the preferences of other countries in its international relations. This concept was adopted under the leadership of Chinese president Hu Jintao during the post - 2000 period. Over the last two decades, China has emerged as a vital force that shapes Sri Lanka’s military, economic, political, and social development. The perceivable reason for Sri Lanka to choose China as a friendly country is largely due to the hard approach adopted by the United States of America and its western allies in their interactions and exchanges with Sri Lanka. However, China’s huge and generous military and economic aid to Sri Lanka has created suspicions and apprehensions in India. The relationship between China and Sri Lanka is not just a friendly bilateral relationship but one that is significant and strategic for geopolitical reasons
Keywords: Culture; Foreign policy; Political values; Relationship; Soft power; Stratergy